Drivers of contracting out in Danish municipalities, 2007-2013: from general to sector-specific explanations - Foged, Søren Kjær (Politica, 2015)
What explains the use of private suppliers in Danish municipalities? The theory normally identifies four main drivers of contracting out: fiscal stress, municipal size, administrative professionals and ideology, but the empirical findings have so far been contradictory. This article builds upon existing research by developing sector-specific hypotheses regarding the association between the four main drivers and the use of private suppliers. The hypotheses are tested via OLS on four sectors: urban development and environment, road surface, home help for elderly and employment. The data comprises all 98 municipalities from 2007 to 2013. The article finds that the effect of fiscal stress, municipal size and ideology varies significantly across the four sectors, whereas the effect of administrative professionals does not seem to be moderated by sector characteristics.